Development of STEAM-Based Learning Tools Integrated with the Techno-Analogy Inquiry Model to Enhance Elementary Students’ Scientific Thinking Skills - Siti Nurfalah; Fadlullah; Yuyu Yuhana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop STEAM-based learning tools integrated with the Techno-Analogy Inquiry (TAI) model to enhance elementary school students’ scientific thinking skills. The novelty of the TAI model lies in its integration of inquiry processes with technology-supported analogical reasoning, which serves as a cognitive bridge to help students connect abstract scientific concepts with familiar real-life experiences. The study employed a Research and Development (R&D) method using the ADDIE model. The participants consisted of 29 fifth-grade students. Data were collected through expert validation of the content, language, and media aspects conducted by four experts using a 4-point Likert scale, as well as through pretest–posttest assessments, observations, and student response questionnaires. The data were analyzed using descriptive statistics, N-gain analysis, and paired-sample t-tests. The results indicate that the developed learning tools are highly feasible, with an average validation score of 87.5%. Students’ scientific thinking skills improved significantly, as reflected in the increase in the mean score from 47 on the pretest to 84 on the posttest. The N-gain score of 0.68 falls within the moderate-to-high category. Furthermore, the paired-sample t-test results revealed a statistically significant difference between the pretest and posttest scores (p < 0.001). These findings suggest that the integration of STEAM, inquiry-based learning, and technology-supported analogical reasoning through the TAI model is effective in enhancing students’ scientific thinking skills and in providing a more meaningful and conceptually accessible learning experience.